Species diversity of small mammals in Lubuk Sembilang Recretional Park, Langkawi Island, Kedah - L., Eileen; Idris, Muhamad Ikhwan; Marni, Wahap; M., Mohamad Jalani; Abdullah, M.T (LESTARI, 2012)
Eileen, L., Muhamad Ikhwan, I., Wahap, M., Mohamad Jalani, M. & Abdullah, M.T.